Food-borne viruses : progress and challenges - Koopmans, M. P. G.; Cliver, Dean O.; Bosch, Albert (Emerging issues in food safety., 2008)
Food-borne viruses are recognized as a major health concern, but their distribution, definition, and impact are poorly understood. The volume Food-Borne Viruses goes a long way in correcting that problem. Written by leading scientists in the field, it brings together the latest knowledge on these viral strains, their detection and control, and associated challenges.